Addition of an immunomodulator can reverse antibody formation and loss of response in patients treated with adalimumab. Issue 2 (16th November 2016) - Ungar, B.; Kopylov, U.; Engel, T.; Yavzori, M.; Fudim, E.; Picard, O.; Lang, A.; Williet, N.; Paul, S.; Chowers, Y.; Bar‐Gil Shitrit, A.; Eliakim, R.; et al.
Summary: Background: Anti‐adalimumab antibodies (AAA) are associated with loss of clinical response (LOR). Addition of an immunomodulator has been shown to reverse immunogenicity and regain response with infliximab monotherapy. Similar data on adalimumab are lacking. Aim: To study the impact of immunomodulator addition on the emergence of AAA and LOR among adalimumab therapy patients. Methods: The databases of three tertiary medical centres were reviewed to identify patients who developed AAA during adalimumab monotherapy with resultant LOR, and received an immunomodulator as a salvage combination therapy. All sera were prospectively analysed using previously described ELISA assays. Clinical response was determined using appropriate clinical scores. Elimination of AAA, designated as 'sero‐reversal', elevation of drug levels and regained clinical response were the sought outcomes. Results: Twenty‐three patients (21 Crohn's disease, and 2 ulcerative colitis) developed AAA with subsequent LOR and were thereafter prescribed an immunomodulator as salvage therapy (thiopurine n = 14, methotrexate n = 9). Eleven patients (48%) underwent sero‐reversal with gradual elimination of AAA, increase in drug trough levels and restoration of clinical response (median time to sero‐reversal 5 months). In 12 patients (52%), immunogenicity and loss of response could not be reversed. There was no difference between responders and nonresponders in the type of immunomodulators used or baseline clinical characteristics. Conclusions: In almost half of inflammatory bowel disease patients developing anti‐adalimumab antibodies and loss of response, established immunogenicity of adalimumab can be gradually reversed by the addition of immunomodulator therapy with restoration of a clinico‐biological response. However, these observations need to be confirmed with larger studies. Abstract : Linked Content This article is linked to Bendtzen and Steenholdt, Ben‐Horin et al, Echarri et al and Ungar et al papers. To view these articles visit https://doi.org/10.1111/apt.13921, https://doi.org/10.1111/apt.13932, https://doi.org/10.1111/apt.15124 and https://doi.org/10.1111/apt.15139 .